Peran Employee Well-Being dalam Meningkatkan Produktivitas Kerja; Perspektif Bisnis Islam - Yanto, Syafri; Azis, Ismi; Adittio Putra, Okka (Program Studi Manajemen Keuangan Syariah, 2026)
The increasingly dynamic and competitive work environment requires organizations not only to focus on performance targets but also to pay attention to employee well-being as a key factor in enhancing work productivity. Employee well-being, which encompasses psychological, social, and physical aspects, plays a strategic role in supporting individual and organizational performance. From an Islamic business perspective, employee well-being is not merely an organizational strategy but also a moral responsibility, reflecting principles such as justice (al-‘adl), balance (tawazun), and trust (amanah) in managing human resources.This study aims to analyze the role of employee well-being in improving employee productivity. This research employs a qualitative approach with a descriptive design. Data were collected through in-depth interviews, observation, and documentation involving active employees within an organization. The data were analyzed using an interactive model consisting of data reduction, data display, and conclusion drawing, with triangulation techniques applied to ensure data validity. The findings reveal that employee well-being significantly contributes to work productivity. Psychological well-being enhances work motivation, work-life balance improves work effectiveness, a supportive work environment fosters collaboration, and physical health directly influences performance. Notably, psychological well-being and work-life balance emerged as the most dominant factors affecting productivity. These findings are consistent with the Job Demands-Resources theory, which emphasizes the balance between job demands and individual resources. In the context of Islamic business values, these results highlight the importance of fostering a humane and balanced work environment that promotes both material and spiritual well-being. The study offers novelty by emphasizing that, in the modern work context, mental well-being and work-life balance have a stronger influence on productivity than other factors. Therefore, organizations are encouraged to implement well-being-oriented policies grounded in ethical and Islamic values to achieve sustainable performance and holistic success (falah).